Sustavski pristup modeliranju s pomoću podvorbenih modela - Mladen Begović; Slavko Šarić (Promet - Traffic&Transportation, 1970)
The paper deals with the system approach to the analysis of transport systems by means of models. The elaborated approach has been applied in the analysis by means of attend ant or service models or system often used as the only possible ones for studying designing and maintenance of transport processes at all levels.